Incorporating Cognitive Linguistic Insights into Classrooms: the Case of Iranian Learners’ Acquisition of If-Clauses - Esmaeel Ali Salimi (Iranian Journal of Applied Language Studies, 2014)
Cognitive linguistics gives the most inclusive, consistent description of how language is organized, used and learned to date. Cognitive linguistics contains a great number of concepts that are useful to second language learners.  If-clauses in English, on the other hand, remain intriguing for foreign language learners to struggle with, due to their intrinsic intricacies. EFL grammar books are paying focal attention to present explanations of if-clauses in terms of their form not meaning, hence not giving attention to their contextual meaning usage. Cognitive linguistic insights on if-clauses discuss their complexity in such a way that could be very beneficial for L2 learners. This study aims to investigate the effect of two different ways of teaching (cognitively-oriented and task-oriented) on learning English if-clauses. A sample of 60 non-English postgraduate students in three groups, two experimental groups (cognitively-oriented and task-oriented) and one control group participated in our study. The results indicated that participants from the cognitively-oriented group performed better than those in task-oriented and control groups and proved a higher degree of comprehending English if-clauses in different contexts. The findings have implications for curriculum and materials developers, as well as the English language teachers in incorporating insights from cognitive linguistics in second language materials.